Managerial Knowledge for Innovation in Argentine MicroSMEs Under the Complexity Paradigm: An Exploratory Study (Global Journal of Management and Business Research, 2025)
Summary- This article presents the results of an exploratory study carried out by the author in relation to the managerial knowledge that prevails in Argentine microSMEs In-depth interviews were conducted with six business leaders during the pandemic in addition to the documentary review in order to a Identify the managerial knowledge of business leaders b Know the importance of considering Argentine microSMEs and their role as a space for training construction transformation updating and application of knowledge management strategies for innovation and c Understanding management knowledge from complexity
Keywords: managerial knowledge; innovation; complexity; microsmes; argentine